Psychosocial and Psychophysiological Effects of Human-Animal Interactions: The Possible Role of Oxytocin - Beetz, Andrea; Uvnäs-Moberg, Kerstin; Julius, Henri; Kotrschal, Kurt (Frontiers in Psychology, 2012)
During the last decade it has become more widely accepted that pet-ownership and animal-assistance in therapy and education may have a multitude of positive effects on humans. Here, we review the evidence from 67 original studies on human-animal interactions (HAI) which met our inclusion criteria with regard to sample size, peer-review and standard scientific research design. Among the well-documented effects of HAI in humans of different ages, with and without special medical or mental health conditions are benefits for: social attention, social behavior, interpersonal interactions and mood; stress-related parameters such as cortisol, heart rate, and blood pressure; self-reported fear and anxiety; and mental and physical health, especially cardiovascular diseases. Limited evidence exists for positive effects of HAI on: reduction of stress-related parameters such as epinephrine and norepinephrine; improvement of immune system functioning and pain management; increased trustworthiness of and trust towards other persons; reduced aggression; enhanced empathy and improved learning. We propose that the activation of the oxytocin system plays a key role in the majority of these reported psychological and psychophysiological effects of HAI. Oxytocin and HAI effects largely overlap, as documented by research in both, humans and animals, and first studies found that HAI affects the oxytocin system. As a common underlying mechanism, the activation of the oxytocin system does not only provide an explanation, but also allows an integrative view of the different effects of HAI.